Diamond morphology CuO nanomaterial's elastic properties, ADMET, optical, structural studies, electrical conductivity and antibacterial activities analysis. Issue 9 (1st August 2022) - Vivek, P.; Rekha, M.; Suvitha, A.; Kowsalya, M.; Steephen, Ananth
Abstract: Copper oxide nanoparticles (CuO NPs) with well-defined diamond-shaped morphology were prepared efficaciously through co-precipitating method. The elastic constants such as Young's modulus (E), Bulk modulus (K), Shear modulus (G), Poisson's ratio and linear compressibility were calculated using the Voigt theory. Furthermore, to quantify sub-atomic descriptors just as to overview nuclear components, Absorption, Distribution, Metabolism, Excretion and Toxicity (ADMET) boundaries, Bioactivity radar and scores are determined utilizing Swiss ADME and ADMET pointers. An assessment on electrical conductivity of CuO nano fluids comprising various concentrations, particle size and nano fluid temperature was made. The nano fluids containing 100 nm CuO has higher electrical conductivity whereas in 150 nm of CuO size, it declines. Nano sized CuO NPs have wide transmission ranges with a UV cutoff wave-length of 235 nm from optical studies. As a function of the wavelength, optical conductivity (σ), Energy gap (Eg), absorption coefficient (α), extinction coefficient (k), refractive index (n) and reflectance (R) were determined. The novel diamond shaped CuO nano particles exhibited virtuous antibacterial action against foodborne pathogens, Escherichia Coli ( E. coli ) and Listeria monocytogenes ( L. monocytogenic ) compounds. Thus, the CuO NPs has potential to be employed in medical field, food packaging applications and in wastewater treatment to control the spread of above-mentioned pathogenic microbes. Graphical Abstract: UF0001